1986
DOI: 10.1111/j.2042-7158.1986.tb04481.x
|View full text |Cite
|
Sign up to set email alerts
|

Ketanserin potentiates the prejunctional inhibitory effect of 5-hydroxytryptamine on rat vas deferens

Abstract: 5-Hydroxytryptamine (5-HT) slightly inhibited the twitch contractions of rat vas deferens caused by single pulse field stimulation at 0.1 Hz. The inhibitory effect of 5-HT was much less in the epididymal portion than in the prostatic portion of the vas deferens. Ketanserin potentiated the prejunctional inhibitory effect of 5-HT and attenuated its stimulatory effect. This potentiation was observable only in the epididymal portion, of the vas deferens. Cyproheptadine and mianserin, but not methysergide, had esse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Cyproheptadine also has mild anticholinergic and antiserotonergic properties (possibly through blocking 5-HT 1A and 5-HT 2A receptors) (48). Animal data suggested that cyproheptadine potentiates the prejunctional inhibitory effect of 5-HT and attenuates its stimulatory effect in the rat and guinea-pig vas deferens (49,50) suggesting peripheral effects. Additionally, it facilitates sexual behavior of the male rat possibly through antiserotonergic effects (51).…”
Section: Cyproheptadinementioning
confidence: 99%
“…Cyproheptadine also has mild anticholinergic and antiserotonergic properties (possibly through blocking 5-HT 1A and 5-HT 2A receptors) (48). Animal data suggested that cyproheptadine potentiates the prejunctional inhibitory effect of 5-HT and attenuates its stimulatory effect in the rat and guinea-pig vas deferens (49,50) suggesting peripheral effects. Additionally, it facilitates sexual behavior of the male rat possibly through antiserotonergic effects (51).…”
Section: Cyproheptadinementioning
confidence: 99%